Add-On Effect of Selenium and Vitamin D Combined Supplementation in Early Control of Graves’ Disease Hyperthyroidism During Methimazole Treatment - Gallo, Daniela; Mortara, Lorenzo; Veronesi, Giovanni; Cattaneo, Simona AM; Genoni, Angelo; Gallazzi, Matteo; Peruzzo, Carlo; Lasalvia, Paolo; Moretto, Paola; Bruno, Antonino; Passi, Alberto; Pini, Andrea; et al. (Frontiers in Endocrinology, 2022)
Prompt and stable control of hyperthyroidism is fundamental to avoid the detrimental effects of thyroid hormone excess, and antithyroid drugs, mainly methimazole (MMI), represent the first-line treatment for Graves’ disease (GD) hyperthyroidism. Decreased serum concentrations of selenium (Se) and calcifediol (25(OH)D, VitD) have been reported in newly diagnosed GD patients in observational studies. Low Se levels might exacerbate oxidative stress by compromising the antioxidant machinery’s response to reactive oxygen species, and low VitD levels might hamper the anti-inflammatory immune response. We performed a randomized controlled clinical trial (EudraCT 2017-00505011) to investigate whether Se and cholecalciferol (VitD) addition to MMI is associated with a prompter control of hyperthyroidism. Forty-two consecutive patients with newly-onset GD and marginal/insufficient Se and VitD levels were randomly assigned to treatment with either MMI monotherapy or MMI combined with Se and VitD. Se treatment was withdrawn after 180 days, while the other treatments were continued. Combination therapy resulted in a significantly greater reduction in serum FT4 concentration at 45 days (-37.9 pg/ml, CI 95%, -43.7 to -32.2 pg/ml) and 180 days (-36.5 pg/ml, CI 95%, -42 to -30.9 pg/ml) compared to MMI monotherapy (respectively: -25.7 pg/ml, CI 95%, -31.6 to -19.7 pg/ml and -22.9 pg/ml, CI 95%, -28 to -17.3 pg/ml, p 0.002). Data at 270 days confirmed this trend (-37.8 pg/ml, CI 95%, -43.6 to -32.1 pg/ml vs -24.4 pg/ml, CI 95%, -30.3 to -18.4 pg/ml). The quality of life (QoL) score was investigated by the validated “Thyroid-related Patient-Reported Outcome” questionnaire (ThyPRO). ThyPRO composite score showed a greater improvement in the intervention group at 45 days (-14.6, CI 95%, -18.8 to -10.4), 180 (-9, CI 95%, -13.9 to -4.2) and 270 days (-14.3, CI 95%, -19.5 to -9.1) compared to MMI group (respectively, -5.2, CI 95%, -9.5 to -1; -5.4, CI 95%, -10.6 to -0.2 and -3.5, CI 95%, -9 to -2.1, p 0-6 months and 6-9 months <0.05). Our results suggest that reaching optimal Se and VitD levels increases the early efficacy of MMI treatment when Se and VitD levels are suboptimal.